2022
DOI: 10.3389/fpsyg.2022.998062
|View full text |Cite
|
Sign up to set email alerts
|

Long-interval intracortical inhibition in primary motor cortex related to working memory in middle-aged adults

Abstract: IntroductionExcitability of the primary motor cortex measured with TMS has been associated with cognitive dysfunctions in patient populations. However, only a few studies have explored this relationship in healthy adults, and even fewer have considered the role of biological sex.MethodsNinety-seven healthy middle-aged adults (53 male) completed a TMS protocol and a neuropsychological assessment. Resting Motor Threshold (RMT) and Long-Interval Intracortical Inhibition (LICI) were assessed in the left motor cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In fact, alterations of ppTMS parameters in neurodegenerative and psychiatric diseases reflect alterations of cognitive rather than motor functions (Benussi et al, 2020, 2018, 2017, 2016; Fatih et al, 2021 ). Given the correlation between LICI and executive functions ( Redondo-Camós et al, 2022 ), whose heavy reliance on frontal processing has been extensively demonstrated ( Peters, 2006 ; Sanger et al, 2001), one could suspect that the Long COVID dysexecutive deficits that have been reported in our sample of patients could be partially explained by pathogenetic processes involving the frontal areas of the brain. Unfortunately, to obtain a measurable TMS output from regions different than the motor cortex is technically demanding.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In fact, alterations of ppTMS parameters in neurodegenerative and psychiatric diseases reflect alterations of cognitive rather than motor functions (Benussi et al, 2020, 2018, 2017, 2016; Fatih et al, 2021 ). Given the correlation between LICI and executive functions ( Redondo-Camós et al, 2022 ), whose heavy reliance on frontal processing has been extensively demonstrated ( Peters, 2006 ; Sanger et al, 2001), one could suspect that the Long COVID dysexecutive deficits that have been reported in our sample of patients could be partially explained by pathogenetic processes involving the frontal areas of the brain. Unfortunately, to obtain a measurable TMS output from regions different than the motor cortex is technically demanding.…”
Section: Discussionmentioning
confidence: 86%
“…SICI is also reduced in central nervous system disorders inducing chronic fatigue ( Liepert et al, 2005 , McDonald et al, 2010 , Vucic et al, 2011 ). In particular, reductions in LICI have been described in patients affected by frontotemporal dementia (FTD, Benussi et al, 2020), and could be related to working memory in healthy middle-aged adults ( Redondo-Camós et al, 2022 ). In addition, a trend for decreased LICI, although not significant, has also been observed in Mild Cognitive Impairment (MCI) due to FTD ( Benussi et al, 2021 ) and in pre-symptomatic genetic FTD ( Benussi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation